KEKERASAN TERHADAP PEREMPUAN: PERSPEKTIF PEMIKIRAN AGAMA DAN SOSIOLOGI - Muhammad Hasbi (IAIN Ponorogo, 2015)
Abstract: Talking about violence, including violence against women is actually talking about social relations in the long span of human history. Violence against women has been done and manifested in various forms, emerging from social, cultural, economic, and political status and even it was done in the name of religion in all levels of society. Social relationships and religious understanding often triggered violence against women. Through sociological and religious perspective, this study tried to explore violence against women which had happened in various public places. In the perspective of religion,Islam has taken a similar position as regards both women and men and their rights should be the same and the identical because Islam brings the mission of equality to the world, and the difference lies only in the presence of piety and devotion to God. In the perspective sociology, both men and women are actually in a balance position. The paradoxical happening of violence against women in the two aspects of knowledge had caused the feminism movement that did not only try to inforce justice and equality between men and women but also tried to reconstruct the role and function of women in order to achieve 'ideal social order’ for the sake of the ideas of equality and justice. At least there should be a movement of feminism which is basically as the transformation of women's movement that aims to create better relationship between men and women.الملخص :إن الحديث عن